Values of Beta-human chorionic gonadotrofin as a risk factor for tubal pregnancy rupture evaluated by histopathology. (April 2014) - Elito Júnior, Julio; Ferreira, Danyelle Farias; Araujo Júnior, Edward; Stavale, João Norberto; Camano, Luiz
Abstract Objective: To evaluate the depth of trophoblastic infiltration in tubal wall in ectopic pregnancy (EP) assessed by histopathology and their correlation with initial values of β-hCG. Methods: A prospective study including 27 patients with diagnosis of EP was realized. The tubal pregnancies were histologically classified according to the depth of infiltration of trophoblastic tissue on the wall of the tube (stage I: limited to mucosa; stage II: reaching the muscularis layer; stage III: complete infiltration of the tubal wall). The comparison between groups for numeric variables was performed by ANOVA. The receiver operating characteristic (ROC) curve was performed to obtain the cutoff value of β-hCG associated with the degree of trophoblast invasion into the wall of the tube evaluated by histology. Results: The mean β-hCG in patients evaluated by histopathology as stage I + II was 2868 mIU/ml and stage III was 11 202 mIU/ml (p = 0.017). β-hCG levels that best predicted for stage III was 2906 mIU/ml, with a sensitivity of 85.7% and a specificity of 69.2%. Conclusion: There is a direct correlation between serum β-hCG and the depth of trophoblast infiltration of the tube wall at histopathology.